Foreign Tourists' Sastifaction Toward Service Quality of Naga Tour Company in The World heritage City of Luangprabang , Luangprabang Province - Soukkhavong, Khamsaming; SIRISACK, Dalivanh; SOUNTHALY, Seng Aloun (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to study: 1) demographic characteristics, 2) the level of satisfaction of international tourists with the service quality of Nagathour Company, and a comparison of personal factors affecting the satisfaction of international tourists. This is a quantitative study using a questionnaire to collect data from a sample of 400 respondents. The data were analyzed using descriptive statistics (frequency, mean, and standard deviation) to describe demographic characteristics and satisfaction in five dimensions. Inferential statistics, including the Chi-square test, Independent Samples t-test, and One-Way ANOVA, were also employed. The research findings reveal that: 1) International tourists who used the services of Nagathour Company exhibited diverse demographic characteristics. The majority were male, middle-aged tourists with a high level of education, a moderate income, and were employed as wage earners. 2) Overall, the level of satisfaction of international tourists with the service quality of Nagathour Company was at the highest level. 3) The comparison of personal factors revealed that income and occupation significantly affected satisfaction in all dimensions. Education level and marital status had partial effects on satisfaction, whereas gender had no impact, at a statistical significance level of 0.05. These findings highlight the necessity of developing services that address the diverse needs of different groups of tourists in order to enhance satisfaction and ensure business sustainability.